Students’ attitudes towards physics in Nine Years Basic Education in Rwanda - Agnes Mbonyiryivuze; Lakhan Lal Yadav; Maurice Musasia Amadalo (International Journal of Evaluation and Research in Education (IJERE), 2021)
This study investigated students’ attitudes towards physics in Nine Year Basic Education (9YBE) in Rwanda. Data were collected from 380 students from Kayonza and Gasabo Districts using a physics attitudes test. Findings illustrated that more than a quarter of participants felt that learning physics is boring. About 39% think that the subject of physics does not relate to the real-world experience. A significant number of participants had negative attitudes towards physics in terms of the effort required for learning. The findings also showed that the overall level for participants in physics problem-solving skills was low. The item-by-item analysis showed that the differences between responses of students from rural schools and their counterparts from urban schools in categories of problem-solving and physics concepts connections and understanding are statistically significant. It was found that many students in rural schools need to know more about the interpretation of a new equation to be able to apply it to a new physics problem.